Influence of nitrogen immersion and NiO nanoparticles on the electrochemical behavior of (Bi, Pb)-2223 superconductor in sodium sulfate solution. Issue 4 (4th June 2018) - Rahal, H.T.; Abdel-Gaber, A.M.; Awad, R.; Abdel-Naby, B.A.
Abstract : Purpose: The paper aims to examine the inhibition effect of NiO nanoparticles and the influence of liquid nitrogen immersion on the corrosion behavior of (NiO)x (Bi1.6 Pb0.4 )Sr2 Ca2 Cu3 O10- δ and (NiO)x (Bi, Pb 2223), where x = 0.00 and 0.05 Wt.% phase superconductor in 0.1 M Na2 SO4 at 30°C. Design/methodology/approach: This study was done using open-circuit potential electrochemical impedance spectroscopy, potentiodynamic polarization curves and chronoamperometry measurements. Findings: Potentiodynamic polarization technique showed that NiO nanoparticles suppress both the anodic and cathodic parts of the polarization curves of (NiO)x (Bi, Pb)-2223 superconductor in 0.1 M Na2 SO4 solution. A significant enhancement in the corrosion resistance of the prepared superconductors is observed on immersing them in liquid nitrogen. This is owing to the fact that immersion in liquid nitrogen increases the volume contraction of the superconductor matrix, causing the shrinkage of the pores and voids present in the samples and thus reducing the active surface area for the dissolution of (NiO)x (Bi, Pb)-2223 superconductor matrix. Originality/value: This paper fulfills the need to investigate the corrosion behavior of superconductors and the influence of liquid nitrogen immersion on such behavior.